TRENDS IN SUPPLY / DEMAND FOR INDONESIAN COAL PERIOD 2005 - 2025 - TRISWAN SUSENO (Puslitbang tekMIRA, 2010)
In 2008, Indonesia mineable coal reserve was recorded around 7.12 billion tons. During that year, around231.18 million tons were exploited. Of such a figure, 69.44 million tons went to domestic market and the rest belonged to export. Yet, in 2025 the need of coal for local consumption may reach 192.33 million tons that include 99.86 million tons for steam power plant, 30.58 million tons for cement industries, and 17.59 million tons for textile industries. Pulp and other industries may consume 2.92 million tons and 41.39 million tons respectively. It is assumed that in 2025, Indonesian coal export will increase to 260.92 million tons Coal export is assumed to increase figuring Coal Mining Agreement as the biggest exporter (94.03%). The rest goes to Mine authority (3.55%) and State-owned Enterprises (2.43%). However, the possibility of unre- corded coal utilization for ether domestic use and export reaches 51.66 million tons. As a result, it is presumed that Indonesian coal production in 2025 is around 504.92 million tons. The production rate during 2010-2025 is 4.9% per annum. According to the above condition, the mineable coal reserve of 7.12 million tons will probably be finished for about 18 years. In addition, the coal-steamed power that operates until now has an age of 26 years. If the reserve is not well-managed, it will immediately be finished in the shorter time. That is why, it needs an anticipative step of a policy concept that can maintain a sustainability of the domestic coal stock by implementing a limited export.